2017
DOI: 10.1186/s40001-017-0286-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of body weight loss and gain on arterial hypertension control: an observational prospective study

Abstract: BackgroundBody weight changes are associated with significant variations in blood pressure (BP). Body mass modifications may, therefore, influence hypertension control in primary care.MethodsPatients with a history of essential arterial hypertension were observed for 12 months. Anthropometric data and clinical BP were evaluated at the time of the recruitment and after 12 months of follow-up. The association between (body mass index) BMI change and BP control was analyzed by logistic regression.ResultsSixteen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
2
18
1
1
Order By: Relevance
“…When the causal link between body weight and the incidence of hypertension is robustly discovered, the implication for controlling the problem of high blood pressure should be raised in the developing world. The actions related to the control of body weight through which hypertension can be restricted include lifestyle changes, nutritional intake, or pharmacological treatments (Dinh et al, 2017;Francischetti and Genelhu, 2007;Lee et al, 2004;Sabaka et al, 2017). Hence, the findings from this study meaningfully provide backgrounds for the public health policies related to the control of overweight and obesity as a solution to the prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 78%
“…When the causal link between body weight and the incidence of hypertension is robustly discovered, the implication for controlling the problem of high blood pressure should be raised in the developing world. The actions related to the control of body weight through which hypertension can be restricted include lifestyle changes, nutritional intake, or pharmacological treatments (Dinh et al, 2017;Francischetti and Genelhu, 2007;Lee et al, 2004;Sabaka et al, 2017). Hence, the findings from this study meaningfully provide backgrounds for the public health policies related to the control of overweight and obesity as a solution to the prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 78%
“…Physical exercise is considered having association with the regression and even prevention of left ventricular hypertrophy (a condition of heart wall's main pumping chamber become thickening and enlargement "LVH"), (Hegde & Solomon, 2015). Other than that, there is an evidence state that weight management having positive feedback with hypertension which weight increase makes higher probability to hypertension and it vice versa, (Sabaka et al, 2017). Furthermore, the overall body weight is not the actual deal who is having a relationship with blood pressure, but the body composition.…”
Section: Resultsmentioning
confidence: 99%
“…This observation contradicted earlier findings by Sebaka et al, who evaluated the effect of body weight loss and gain on arterial hypertension control. Their study indicated that weight increase was directly proportional to poor hypertension control in obese and overweight participants [33]. The difference in observation could be due to the difference in the period of observation in the two studies.…”
Section: Discussionmentioning
confidence: 96%